A longitudinal analysis of shooter games and their relationship with conduct disorder and cself-reported delinquency. (May 2018) - Smith, Sven; Ferguson, Chris; Beaver, Kevin
Abstract: Purpose: Despite several decades of research, little scholarly consensus has emerged regarding the role of violent video games in the development of youth psychopathology or crime. Method: The current study employed the Avon Longitudinal Study of Parents and Children longitudinal dataset to examine the impact of the shooter game genre ownership in childhood on later adolescent conduct disorder and criminal behavior. Analysis: Multivariate Poisson regressions with the robust estimator correlation matrix were performed comparing effects of independent and confounding variables. Results: Results revealed that early childhood mental health symptoms at age seven related to ADHD, depression and early conduct disorder predicted criminal behavior at age fifteen. Male gender also predicted criminal behavior at age fifteen. However, exposure to shooter games did not predict adolescent conduct disorder or criminal behavior. Conclusion: We have found support that suggests that the role of violent video games in the development of youth psychopathology or crime is very little if any. Lack of a relationship between exposure to shooter games and later conduct and criminal behavior problems may be understood within the context of the Catalyst Model.